PERAN EMOTIONAL INTELLIGENCE, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. BANK PEMBANGUNAN DAERAH JAWA TIMUR TBK. CABANG UTAMA SURABAYA - Michelle Hary Putrani; Sumiati (CV. Adiba Aisha Amira, 2026)
Workplace Organization and Motivation in Relation to Employee Performance at PT. Bank Pembangunan Daerah Jawa Timur Tbk., Surabaya Main Branch Office. This study was conducted to understand the simultaneous and partial effects of these three variables, as well as to identify the most important factors affecting employee performance. The background of this study is the importance of human resources in the banking industry, where employee productivity is crucial to achieving business goals and improving service quality. This study uses a quantitative approach with a survey method. Data were collected via questionnaires distributed to employees and analyzed using multiple linear regression, t-tests, and F-tests. Before being used for data collection, the validity and reliability of the research instruments were evaluated. The research results indicate that Emotional Intelligence has a positive and significant effect on employee work performance, showing that the ability to control and manage emotions contributes to improved work performance. Organizational Culture also has a positive and significant effect, indicating that workplace standards, norms, and regulations support employee discipline and productivity. Furthermore, Work Motivation is identified as the most significant variable affecting employee productivity. Together, these three variables have a significant impact on worker productivity, which means increasing productivity requires a strong organizational culture, high employee motivation, and good emotional intelligence.